2022
DOI: 10.3390/jcm11102846
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Measurement in Childhood Glaucoma under Standardized General Anaesthesia: The Prospective EyeBIS Study

Abstract: Objective: We aimed to compare intraocular pressure (IOP) measurements using iCare® PRO rebound tonometry (iCare) and Perkins applanation tonometry (Perkins) in childhood glaucoma subjects and healthy children and the influence of anaesthesia depth, age and corneal thickness. Material: Prospective clinical, case-control study of children who underwent an ophthalmologic examination under general anaesthesia according to our protocol. Children were 45.45 ± 29.76 months old (mean ± SD (standard deviation)). Of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Previous literature has reported RBT to overestimate IOP in children with 13,14,15,16 and without glaucoma. 12,21 This study data correlate with these findings, regardless of the clinical group.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Previous literature has reported RBT to overestimate IOP in children with 13,14,15,16 and without glaucoma. 12,21 This study data correlate with these findings, regardless of the clinical group.…”
Section: Discussionmentioning
confidence: 81%
“…12 In the study analysis, the difference in IOP between RBT and AT was most pronounced in the PCG group. Strzalkowska et al 13 reported a mean IOP difference between RBT and AT of 6.0 mmHg ± 6.1 mmHg in their study investigating the optimal timing of measuring IOP in children with and without PCG undergoing anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the article entitled "Intraocular pressure measurement in childhood glaucoma under standardized general anesthesia: the prospective EyeBIS study", Alicja Strzalkowska et al [12] addresses the important topic of the IOP measurement in children. The authors compared the IOP measurements taken with the iCare PRO rebound tonometer and Perkins applanation tonometer in glaucomatous and healthy children (mean age of 45 ± 30 months) under general anesthesia.…”
mentioning
confidence: 99%